Serum HE4 and CA-125 as Combined Biomarkers for Early Diagnosis of Ovarian Carcinoma - Saira Kiran, Rehana Batool, Habibah Nadeem, Hamna Rizwan, Shazia Hameed, Tahira Rizwan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Early detection of epithelial ovarian carcinoma remains a major clinical challenge dueto its asymptomatic progression and lack of reliable single diagnostic biomarkers. This prospective case–control study evaluated